Faith On The Move: A Deep Dive Into MuslimTraveller Food Experiences Through the Lens of IR 4.0 - Adlin Masood; Umi Hamidaton Mohd Soffian Lee; Nur Aqilah Hazirah Mohd Anim (Universal Publishers - Boca Raton, Florida, USA, 2026)
Indexed by ERA